Influence of Innovation Strategy Model on Improving Organizational Performance of the Regional Government in Indonesia (Architecture Image Studies, 2025)
The performance of Regional Government organizations in Indonesia must always be improved by creating ideas or innovations to gain the trust of the community and respond to the demands of current developments. This research aims to analyze the picture of performance, which includes the external environment, internal environment, digital innovation, and digitalization of public services that influence it. This is because the performance achievements of Regency/City Regional Government organizations in Indonesia are still uneven, and there are still problems that need to be corrected. So it is very interesting to research. The design and methods in this research use quantitative research methods, including survey methods. The population studied was 100 Regency/City Regional Governments in the Provinces of West Java, Central Java, and East Java. Determining the sample/unit of analysis uses a saturated sample/census technique so that all members of the population become the research sample. The technical analysis uses PLS-SEM (Partial Least Squares-Structural Equation Model). The findings and results of the research show that the external environment has a negative and significant effect on the digitalization of public services and has a positive but not significant effect on digital innovation, the internal environment has a positive and significant effect on digital innovation and has a positive and significant effect on the digitalization of public services, digital innovation has a positive effect and significant impact on the digitalization of public services and has a positive and significant effect on the performance of Regional Government organizations, however the performance of Regional Government organizations is not influenced by the digitalization of public services either directly or as an intervening variable.The purpose of this research is to build a hypothetical model regarding the influence of competency level, job satisfaction level, strength of employer branding, and employee engagement on the performance level of midwives in Tasikmalaya City. The results of the research can be applied by the Health Service to achieve increased performance of midwife health workers in order to fulfill one of the people's basic rights, namely the right to obtain maximum health services.